PENDAMPINGAN PENANGANAN SAMPAH PLASTIK UNTUK MINIMASI DAMPAK PENCEMARAN LINGKUNGAN DI UNIVERSITAS SANG BUMI RUWA JURAI BANDAR LAMPUNG - yuli darni; Lia Lismeri; Herti Utami; Simparmin Ginting; Aris Setiawan; Nindya Kusumawardhani; Muhammad Hussein (Jurnal Pengabdian Kepada Masyarakat Sakai Sambayan, 2026)
The community service activity at Sang Bumi Ruwa Jurai University (Saburai) aims to improve and develop initiatives for plastic waste management to minimize environmental pollution and generate products with higher economic value. Through this program, students learn how to sort and manage plastic waste within the campus environment. This activity directly impacts plastic waste handling efforts. The methods applied in this program include socialization and training on waste management. During the socialization, the utilization and management of plastic waste are briefly explained using the concepts of reduce, reuse, and recycle. Training sessions are provided to students, staff, and cleaning personnel at Saburai University, focusing on plastic waste sorting techniques. The activities take place at Saburai University, Bandar Lampung, targeting primarily the students and staff, who are then expected to disseminate the knowledge to the surrounding community. The expected outcome is that partners are able to manage plastic waste more efficiently and enhance its economic value. This initiative represents a positive contribution to one of the government’s programs in environmental protection and efforts to minimize waste and pollution.